The role of the IRS1 gene (rs2943640) in the comorbid course of type 2 diabetes mellitus, obesity and arterial hypertension - I. Vivsiana; H. Habor; M. Marushchak (Kazimierz Wielki University, 2021)
Type 2 diabetes mellitus (T2DM) affects more than 7 million people, resulting in 2.8 million hospitalizations and more than 300,000 deaths reported annually. Current scientific data indicate that among the world's population, arterial hypertension (AH) and type 2 diabetes mellitus (T2DM) after obesity are among the leading factors of cardiovascular risk. Aim of research: was to establish the prevalence of the IRS1 gene (rs2943640) polymorphism in patients with T2DM in combination with obesity and arterial hypertension/ Material and research methods. The study involved 33 type-2 diabetic patients hospitalized to the Endocrinology Department of Ternopil University Hospital (Ternopil, Ukraine) in 2019-2020 and 10 healthy individuals. Inclusion criteria: clinical, laboratory and instrumental signs of T2DM, AH and obesity. Exclusion criteria from the study: signs of clinically significant neurological, mental, renal, hepatic, immune, gastrointestinal, urogenital disorder; injuries of the musculoskeletal system, skin, sense organs, endocrine system (except T2DM); or uncontrolled hematologic diseases; acute pancreatitis, unstable or life-threatening heart disease; patients with malignant neoplasms who have not been in complete remission for at least 5 years, medication (drug) dependence, and alcohol dependence. T2DM diagnoses were confirmed according to the 2019 Recommendations of the American Diabetes Association (ADA). The diagnosis of arterial hypertension (Stage I) was made according to 2018 ESC/ESH Guidelines for the management of arterial hypertension. Systolic (140-159 mmHg) and/or diastolic (90-99 mmHg) blood pressure were considered as the presence of Stage I AH. Left ventricular hypertrophy was confirmed by an electrocardiogram. Genomic DNA was extracted from peripheral blood leukocytes using a commercially available DNA isolation kit (QIAamp Blood DNA Mini Kit, QIAGEN, Germany). The IRS-1 gene rs2943640 C>A polymorphism was genotyped using the TaqMan real-time PCR method (Applied Biosystems, Foster City, CA, USA). Statistical analysis of the data was performed using the software STATISTICA 7.0. Results. The frequency distribution of the IRS1 gene (rs2943640) polymorphisms and the assessment of compliance with the Hardy - Weinberg equilibrium were performed in the experimental and control groups. It was found that the frequencies of the genotype responsible for C/A polymorphism of the IRS1 gene at T2DM, T2DM with obesity and in the combined course of T2DM with obesity and arterial hypertension did not deviate from the Hardy - Weinberg equilibrium (p> 0.05), while in the control group the selected sample did not correspond to the general population. The corresponding frequencies for the genotypes of the IRS1 gene were as follows: 66.7% for C/A and 33.3% for A/A in the experimental group 1; 42.9% for C/C, 57.1% for C/A in group 2; 47.1% for C/C, 29.4% for C/A and 23.5% for A/A in group 3 and 100.0% for C/A in the control group. Analysis of allele frequencies for the IRS1 gene in patients with T2DM and comorbidity showed that in patients with T2DM the A allele prevailed (2.0 times), while in patients with T2DM + obesity and T2DM + obesity + arterial hypertension - the C allele. It should be noted that the C allele and the A allele were equally present in the control group. Analysis of the odds ratio for IRS1 gene genotypes (rs2943640) in patients with T2DM, T2DM and obesity showed no statistically significant relationship between factor (presence of C or A alleles) and disease onset (p> 0.05). At the same time, the significant influence of the C/A genotype of the IRS1 gene on the development of T2DM combined with obesity and arterial hypertension (p <0.05) was established. This is confirmed by a significant difference in the dominant model of inheritance of the IRS1 gene only in the group with the combination of T2DM with obesity and arterial hypertension compared with the control group (reliability coefficient for the chi-square p <0.001). Conclusion. The presence of the C allele of the IRS1 gene (rs2943640) in both homozygous and heterozygous states may increase the risk of comorbid course of T2DM, obesity and arterial hypertension.